2011
DOI: 10.1177/0042098011427183
|View full text |Cite
|
Sign up to set email alerts
|

Political Decision-making and the Local Provision of Public Goods: The Case of Municipal Climate Protection in the US

Abstract: The municipal political decision-making dynamic has typically been studied in regard to the provision of locally public goods and services whose benefits, while diffuse, are tied to a particular geography. This research extends current knowledge by empirically examining the local production of a global public good: climate protection. It utilises an original nation-wide dataset on the greenhouse gas-reducing activities that have been implemented by city governments in the US. These data enable the development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
120
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(125 citation statements)
references
References 34 publications
3
120
0
1
Order By: Relevance
“…Some studies find capacity to be a key predictor of municipal adoption of sustainability policies (Krause, 2011(Krause, , 2012Lubell, Feiock, & Handy, 2009) while others do not (e.g., Svara et al, 2013). Capacity includes agency resources: financial, expertise, staffing and time.…”
Section: Factors Of Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies find capacity to be a key predictor of municipal adoption of sustainability policies (Krause, 2011(Krause, , 2012Lubell, Feiock, & Handy, 2009) while others do not (e.g., Svara et al, 2013). Capacity includes agency resources: financial, expertise, staffing and time.…”
Section: Factors Of Implementationmentioning
confidence: 99%
“…The recent literature on the factors of local environmental sustainability implementation focuses on the factors that are easiest to assess, such as socio-demographics factors, form of government and state mandates (e.g., Krause, 2011Krause, , 2012Krause, , 2013Svara et al, 2013;Wang et al 2012). Yet, institutional barriers may be the most salient barriers because "sustainability is fundamentally a political rather than technological or design problem" (.…”
Section: Introductionmentioning
confidence: 99%
“…For example, we may hypothesise that an investment in institutions will improve policy success. Previous research has shown that institutional capacity within city governments is a predictor of climate-change policy action: dedicated staff has the greatest effect on local action in the United States (Krause 2012); separate offices dedicated to climate change (Feiock et al 2010) and staff commitment (Wang 2013) have also been found to lead to more policy effort. Does the institutionalisation of science and expertise lead to similar levels of policy success?…”
Section: Discussionmentioning
confidence: 99%
“…The persistent lack of negotiated global action on climate change and rise in subnational action has generated a substantial body of research examining how and why localised action on climate change takes place (Bulkeley and Betsill 2005, Romero-Lankao 2007, Anguelovski and Carmin 2011, Jones 2012, Krause 2012, Hughes 2013). In part, these studies have found that one of the requirements of effective climate-change policy at the city scale is that local governments be able to access science and information such as future climate projections, greenhousegas inventories, and climate vulnerability assessments.…”
mentioning
confidence: 99%
“…Barbour and Deakin, 2012;Chapin, 2012;DeGrove, 2005;Rabe, 2009). To this end, anti-Agenda 21 actors view the state as the key sovereign political unit for dismantling sustainability planning efforts, particularly as cities nationwide pursue climate action planning (Krause, 2012).…”
mentioning
confidence: 99%